Creativity Process and Personality - Gross, Larry (Public Domain Series, 2023)
Before arriving in the field of communication, Larry Gross was a psychology student at Brandeis University; Creativity: Process and Personality was Gross's undergraduate thesis at Brandeis, completed in 1964. This mediastudies.press edition is the initial publication of that undergraduate thesis, with a new preface by Gross himself. Creativity: Process and Personality finds Gross exploring the nature of creativity by interviewing some of the era's most noteworthy experts in psychology, including Herbert Simon, Milton Rokeach, Abraham Maslow, David McClelland, Jerome Bruner, and B. F. Skinner. The result of Gross's interviews is a nuanced and multi-perspectival set of interlocking chapters, each of which probes the psychological, social, and cultural aspects of creativity. Creativity: Process and Personality remains a provocative consideration of how creativity takes form, while also operating as a revealing snapshot of mid-twentieth century psychological thought.